The Behavior of a 1.4301 Stainless Steel Subjected to Cryogenic Temperatures. (2015) - Crismaru, Ionut Vasile; Dragomir-Stanciu, Daniel; Atanasiu, Marius Vasile; Pintilei, Geanina Laura
Abstract: Usually equipments that work at low and cryogenic temperatures are made of stainless steel due to their good mechanical and anti corrosion properties. The best stainless steels for this kind of applications are the ones that present an austenitic microstructure. The austenitic microstructure is the most plastic phase of the Fe-Fe3 C alloys but this gives it a very good resilience at low temperature. This paper analysis the behavior of a 1.4301 stainless steel subjected to prolonged exposure to cryogenic temperatures and thermal cycles of cooling to cryogenic temperatures and heating to room temperature. The cryogenic temperatures were obtained by immersing the samples in liquid air which has a temperature of -196 °C. The samples were analyzed using scanning electron microscopy, optical microscopy and x-ray diffraction.